Effects of nutrient content claims, sports celebrity endorsements and premium offers on pre-adolescent children's food preferences: experimental research - Dixon, H.; Scully, M.; Niven, P.; Kelly, B.; Chapman, K.; Donovan, Robert; Martin, J .; Baur, L.; Crawford, D.; Wakefield, M. (Wiley-Blackwell Publishing Ltd, 2014)
Objectives: To assess pre-adolescent children's responses to common child-oriented front-of-pack food promotions.Methods: Between-subjects, web-based experiment with four front-of-pack promotion conditions onenergy-dense and nutrient-poor (EDNP) foods: no promotion [control]; nutrient content claims; sports celebrity endorsements (male athletes) and premium offers. Participants were 1302 grade 5 and 6 children (mean age 11 years) from Melbourne, Australia. Participants chose their preferred product from a randomly assigned EDNP food pack and comparable healthier food pack then completed detailed product ratings. Child-oriented pack designs with colourful, cartooned graphics, fonts and promotions were used.Results: Compared to the control condition, children were more likely to choose EDNP products featuring nutrient content claims (both genders) and sports celebrity endorsements (boys only). Perceptions of nutritional content were enhanced by nutrient content claims. Effects of promotions on some product ratings (but not choice) were negated when children referred to the nutrition information panel. Premium offers did not enhance children's product ratings or choice